2005
DOI: 10.1108/09544780510627660
|View full text |Cite
|
Sign up to set email alerts
|

TQM implementation and students' satisfaction of academic performance

Abstract: PurposeThe aim of the study is to develop a TQM model of academic excellence and empirically establish a relationship between TQM implementation and students' satisfaction of academic performance.Design/methodology/approachA sample of students from ISO and non‐ISO engineering institutions from South India has been taken for the study. Statistical measures like mean, t‐test, correlation and regression analysis were used.FindingsThe results reflect that ISO 9001:2000 engineering institutions are moving towards t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
97
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 58 publications
10
97
0
4
Order By: Relevance
“…M. Hill, 1995;Y. Hill et al, 2003;Mai, 2005;Negricea et al, 2014;Ravindran and Kalpana, 2012;Roman, 2014;Sakthivel et al, 2005;Wang and Tseng, 2011;Wilkins et al, 2013; were also found to significantly affect student satisfaction with quality of higher education services. Similarly, many earlier studies (de Kleijn et al, 2012;Harman, 2003;Khosravi et al, 2013;Munteanu et al, 2010;Sutton and Sankar, 2011;Zhao et al, 2007) underlined the importance of academic advising services on student satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…M. Hill, 1995;Y. Hill et al, 2003;Mai, 2005;Negricea et al, 2014;Ravindran and Kalpana, 2012;Roman, 2014;Sakthivel et al, 2005;Wang and Tseng, 2011;Wilkins et al, 2013; were also found to significantly affect student satisfaction with quality of higher education services. Similarly, many earlier studies (de Kleijn et al, 2012;Harman, 2003;Khosravi et al, 2013;Munteanu et al, 2010;Sutton and Sankar, 2011;Zhao et al, 2007) underlined the importance of academic advising services on student satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Campus facility would enhance the process of teaching and learning [9] which included well equipped lecture halls and rooms, efficient library services, well equipped and maintained computer and practical labs, transportation, C840…”
Section: Campus Facilitymentioning
confidence: 99%
“…Top management must not only strive hard for an effective tqm system in education, but also manage and maintain all available resources so that an effective tqm in education environment would be realized in their institution [1,9]. …”
Section: Commitment From Top Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…This study focuses solely on the students' perspective because they are the ones who should measure and judge the quality of service since they are the recipients of the services (Zairi 1995;Sakthivel and Rajendran 2005).…”
mentioning
confidence: 99%